2018
DOI: 10.1111/scs.12560
|View full text |Cite
|
Sign up to set email alerts
|

Exploring complaints by female and male patients at Swedish hospitals using a probabilistic graphical model

Abstract: Using a Bayesian network, this article suggests that complaints in health care should be more holistically understood and the factors should be viewed as interconnected. This article addresses complaints as an important source of identifying not only perceived healthcare deficiencies and sex disparities, but also improvement suggestions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
(27 reference statements)
0
4
1
Order By: Relevance
“…Previous studies have found that the majority of complaints in the NHS have focused on communication and were targeted at primary care givers [4,15,17]. Our study, however, shows a significant shift; where over a third of complaints related to delays and cancellations and were aimed at management.…”
Section: Resultscontrasting
confidence: 57%
See 1 more Smart Citation
“…Previous studies have found that the majority of complaints in the NHS have focused on communication and were targeted at primary care givers [4,15,17]. Our study, however, shows a significant shift; where over a third of complaints related to delays and cancellations and were aimed at management.…”
Section: Resultscontrasting
confidence: 57%
“…Patients expect a good encounter to focus on their individual healthcare needs, and person-centred care has shown to positively impact healthcare interactions, outcomes, and patient satisfaction [1]. Furthermore, Eriksson and colleagues argued that communication is the basis of the patient-caregiver relationship and reiterated that inadequate time has a negative impact on this [15]. Improving the efficiency of patient encounters by acting on patient feedback can improve patient outcomes not only by improving the quality of care but also by improving patient engagement with health services and adherence to treatment [16].…”
Section: Resultsmentioning
confidence: 99%
“…Complainants7 20 70 perceive social and institutional issues as critical aspects of care quality. Yet, non-clinical complaints are unlikely to be prioritised by care providers and regulators 20 26 69 94. If complaints are strictly secondary to internal quality and safety data sets, they may not reveal the issues that are critical to patients but not to staff.…”
Section: Resultsmentioning
confidence: 99%
“…There are differences in the literature in terms of gender, age range, educational status, and occupation of the complainant. [10,[14][15][16][17][18][19][20][21][22] We attribute this to the type of health institutions, sample size, time zone, data source, and socio-cultural structure of the society. When we examined which unit the patients applied to, it was determined that 58.7% (n=813) had applied to the patient rights unit.…”
Section: Discussionmentioning
confidence: 99%